Measles immunisation rates and the good practice allowance. - Mant, D; Phillips, A; Knightley, M (1986)
The recent discussion document on primary health care proposes that a good practice allowance is paid to general practitioners based in part on the uptake of immunisation by patients. The variation between and the validity of practice immunisation rates for measles as determined by one district health authority's child health computer are assessed. In areas of low population mobility district health authority rates may be sufficiently accurate to base a good practice allowance on but should not be used until the social environment of each practice can also be characterised. In areas of high mobility intermittent surveys may be a preferable method of auditing performance.